(untitled) (Journal of Education and Development, 2021)
This study assessed the influence of humanitarian assistance post conflict intervention measures on reconstruction of public teacher training colleges in South Sudan. The study adopted a descriptive cross-sectional survey design and a total of 1953 respondents including the principals, tutors and teacher students from 3 registered and operational teacher training colleges in South Sudan. Stratefied random sampling technique was used to select 321 respondents as the sample size. Pilot study was conducted to asses validity and reliability of the instruments of the study. The study collected primary data using questionnaires and interview guides. The analysis was conducted using descriptive statistics like frequencies and percentages. Besides descriptive statistics, the study used inferential statistics including correlation and regression analysis. The results were presented using Tables and Figures. The study established that humanitarian assistance post conflict intervention measures (p<0.05) were all significant. Therefore, the study rejected the formulated hypothesis in favour of the alternative hypotheses since their p-values were all less than 0.05 as 5 per cent was considered as the level of significance in the study. Based on regression beta coeffecients and the p-values of the individual variables, the study concluded that humanitarian assistance post conflict intervention measures had positive and significant influence on reconstruction of public teacher training colleges. The study recommended that efforts or reconstructing teachers training college cannot bear fruits unless stakeholders including the humanitarian organizations have been actively involved.